Nghiên cứu ảnh hưởng của nanoclay cloisite 30B đến tính chất cơ học của màng polyme epoxy DER 671X75 - Huy Cường, Huỳnh Lê; Diệu, Trần Vĩnh; Thành, Nguyễn Đắc; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2016)
In this study, two techniques of mechanical stirring with elevated speed and ultrasonic vibration at different period of time were used for dispersion of nanoclay Cloisite 30B in epoxy resin DER 671X75. Results of X-ray diffraction, scanning electron microscopy and optical images showed that optimum conditions for dispersion of nanoclay Cloisite 30B in epoxy resin DER 671X75 were mechanical stirring at speed 2000 rpm for 35 hrs or mechanical stirring at speed 1000 rpm for 15 mins followed by ultrasonic vibration for 40 mins. Nanoclay Cloisite 30B content of 2 % in epoxy resin DER 671X75 improved mechanical and thermal properties of polymer film coating, especially impact strength increased from 5 to 62.5 kG.cm. Keywords. Nanoclay Cloisite 30B, epoxy DER 671X75, nanocomposites